Use of pharmacokinetic/pharmacodynamic biomarkers to support rational cancer drug development. (October 2007) - Sarker, Debashis; Pacey, Simon; Workman, Paul
The process of drug development in oncology has struggled to alter at a pace in keeping with the rapid discovery and testing of agents that act on a wide variety of molecular targets. The rational development of such agents requires an understanding of drug effect(s) on their purported target. It is likely that testing these drugs in a framework designed to examine cytotoxic agents will fail to establish their full potential. We discuss how data gained from biomarker investigation might impact on drug development and provide examples that highlight the development, validation and use of pharmacokinetic, and especially pharmacodynamic biomarkers as drug development moves from the laboratory into clinical testing. The challenges of performing assays to satisfy regulatory requirements have been the subject of much debate. We recommend the implementation of appropriate, fit-for-purpose biomarkers in clinical trials of all new cancer drugs.